2013
DOI: 10.7448/ias.16.3.18717
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and drivers of HIV stigma among health providers in urban India: implications for interventions

Abstract: IntroductionHIV stigma inflicts hardship and suffering on people living with HIV (PLHIV) and interferes with both prevention and treatment efforts. Health professionals are often named by PLHIV as an important source of stigma. This study was designed to examine rates and drivers of stigma and discrimination among doctors, nurses and ward staff in different urban healthcare settings in high HIV prevalence states in India.MethodsThis cross-sectional study enrolled 305 doctors, 369 nurses and 346 ward staff in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(104 citation statements)
references
References 39 publications
8
90
2
Order By: Relevance
“…The perpetuation of stigmatizing attitudes and discrimination by healthcare workers has been widely reported, ranging from issues of confidentiality, verbal harassment to denial of treatment [4, [27][28][29]. As a result, it is not unexpected that respondents in the present study who came in contact with the healthcare system and were advised by health personnel to do a HIV test were significantly more likely to have reported discrimination than those who advised themselves.…”
Section: Discussionsupporting
confidence: 49%
“…The perpetuation of stigmatizing attitudes and discrimination by healthcare workers has been widely reported, ranging from issues of confidentiality, verbal harassment to denial of treatment [4, [27][28][29]. As a result, it is not unexpected that respondents in the present study who came in contact with the healthcare system and were advised by health personnel to do a HIV test were significantly more likely to have reported discrimination than those who advised themselves.…”
Section: Discussionsupporting
confidence: 49%
“…20 Marfatia et al 20 showed that 25% HIVinfected individuals in India had been refused medical care due to strong evidence of stigma at workplace, and 74% of PLWHA did not disclose disease status for fear of discrimination and community retaliation. Surprisingly, stigma and discrimination have also been found to be very common in health setups as pointed by Ekstrand et al 21 Given such a situation, it becomes imperative in many ways, for PLWHA to adopt defense strategies to cope with an inherent stress associated with stigmatization. Freud in his psychoanalytical theory defined defense mechanisms as unconscious psychological strategies brought into play by various entities to cope with reality and to maintain self-image.…”
Section: Indian Journal Of Clinical Medicine 00(0)mentioning
confidence: 99%
“…HIV/AIDS stigma among health professionals is common and can be a barrier to effective access to treatment (Ekstrand, Ramakrishna, Bharat, & Heylen, 2013; Varas-Díaz, Malavé-Rivera, & Cintrón-Bou, 2008; Varas-Diaz & Neilands, 2009; Varas-Diaz, Neilands, Malave Rivera, & Betancourt, 2010). Although research has been nimble to respond in developing strategies to document HIV/AIDS stigma among health professionals, the development of effective interventions to reduce it has lagged behind.…”
Section: Introductionmentioning
confidence: 99%